1970
DOI: 10.3329/bjch.v30i1.6178
|View full text |Cite
|
Sign up to set email alerts
|

The Seroprevalence of Hepatitis B Virus Among Children Attending Urban and Rural Hospitals

Abstract: Objectives: This study was conducted to a) find out and compare the period prevalence of HBsAg in children attending outdoor and indoor of an urban and a rural hospital b) determine the risk factors for Hepatitis B surface antigen positivity. Materials and Methods: Three hundred and twenty three children were included in this study. Among them 162 attended an urban hospital and 161 attended a rural hospital. Collected sera were examined for HBsAg by ELISA method in a standard laboratory. Results: Among the 162… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…What complicates this picture is children in the age group 5–15 consistently show a significantly higher prevalence than under 5 children. This conclusion is based on the findings from four different study populations, differing in region (urban vs. rural) and socioeconomic background [ 1 , 3 , 13 , 18 ]. Based on prevalence data alone, while the high mean prevalence among children <15 (5.6%) does indicate the possibility of significant vertical transmission, a closer look at children of different age groups makes this inference less clear-cut.…”
Section: Vertical Transmission Of Hepatitis B Virus In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…What complicates this picture is children in the age group 5–15 consistently show a significantly higher prevalence than under 5 children. This conclusion is based on the findings from four different study populations, differing in region (urban vs. rural) and socioeconomic background [ 1 , 3 , 13 , 18 ]. Based on prevalence data alone, while the high mean prevalence among children <15 (5.6%) does indicate the possibility of significant vertical transmission, a closer look at children of different age groups makes this inference less clear-cut.…”
Section: Vertical Transmission Of Hepatitis B Virus In Bangladeshmentioning
confidence: 99%
“…The bar heights are factors of the normalized sample sizes of each study. The sample sizes ranged from 130 [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] to 43,312 [ 8 ]. Studies done on voluntary blood donors and pregnant women have not been included here, since they form a substantial enough group to merit their own discussion.…”
Section: Figurementioning
confidence: 99%
“…The included 15 studies with a total sample size of 60 496 reported the prevalence of hepatitis B in Bangladesh and the characteristics of all studies are presented in Table 1. All the included articles [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] were cross-sectional studies and conducted throughout the period ranging from 1995 to 2017. The smallest sample size was 130 [14] and the largest sample size was 43 213 [26].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The hepatitis B vaccine birth dose was not introduced into the childhood vaccination schedule; 71% of births in Bangladesh occurred at home in 2011, which is a logistic barrier to administering a timely birth dose of hepatitis B vaccine. 16 Although data on the burden of chronic HBV infection in Bangladesh are limited, previous small-scale studies evaluated the prevalence of HBsAg, a marker of chronic HBV infection, to be 3–7% among the general population 17 20 and 1.5–12% among children aged < 5 years. 17 , 18 , 20 …”
Section: Introductionmentioning
confidence: 99%